Adsorption and Separation of Small Hydrocarbons on the Flexible, Vanadium-Containing MOF, COMOC-2 - Couck, Sarah; Van Assche, Tom R C; Liu, Ying-Ya; Baron, Gino V; Van Der Voort, Pascal; Denayer, Joeri F M (Langmuir, 2015)
COMOC-2, a flexible vanadium-containing metal-organic framework, was investigated for its adsorption and separation properties of light hydrocarbons. COMOC-2 is an extended version of the MIL-47 framework with 4,4'-biphenyldicarboxylic acid linkers instead of terephthalic acid. Adsorption isotherms of methane to propane, ethylene, and propylene were determined with a gravimetric uptake technique at temperatures between 281 and 303 K. A pronounced breathing effect was observed (in contrast to the more rigid MIL-47 framework) in which the adsorption capacity increases by more than a factor of 2 at a given breathing pressure. The breathing pressure decreases with increasing hydrocarbon molecular weight. The typical two-step isotherms are nearly identical for alkanes and alkenes, in accordance with the nonpolar nature of the material. Binary isotherms of ethane and propane were also measured with the gravimetric uptake technique at different temperatures and total pressures. The mixture isotherms and breathing transition pressures were predicted by relying on the osmotic framework adsorbed solution theory (OFAST). Finally, the separation potential of COMOC-2 for ethane/propane mixtures was looked into using breakthrough experiments for different compositions and different pressures.